High Resolution Computed Tomography (HRCT) Evaluation of Suspected Interstitial Lung Disease Cases. - Sunil M; Mishal Mohammed; Y Thiruvarul (Asian Journal of Medical Radiological Research, 2019)
Background: Interstitial lung disease (ILD) refers to a large group of diseases that causes scarring of lung tissue. Diagnosis of exact etiology of ILD is usually by clinico-radiologic-pathologic correlation. HRCT of Lung plays a crucial role in diagnosis of etiology of ILD & determining prognosis. Objective: To describe the HRCT findings in clinically suspected cases of ILD and to compare the role of HRCT with Chest X ray in diagnosis of ILD. Subjects and Methods: A descriptive study was conducted among 50 consecutive, consenting patients with clinical suspicion of interstitial lung disease. History and clinical details of all study participants were noted and first examined with chest radiography and then exposed to HRCT. The data thus collected was properly coded and entered in Microsoft Excel and analysis was done using the software SPSS version 16.0. Results: Mean age of the study population was 48.84 years (SD=14.46).60% of the study participants were males. Specific diagnoses could be made in 25.7% of abnormal case with radiograph and clinical correlation and in 57% with HRCT and clinical correlation. Most common pattern identified was reticular (60%) and most common anatomical area of involvement identified was lower lobe (54.28%). Most common etiology among the cases was idiopathic pulmonary fibrosis (20%) followed by sarcoidosis (11.4%). Conclusion: Idiopathic pulmonary fibrosis, sarcoidosis and Hypersensitivity pneumonitis along with non specific type were the most frequent types of ILD identified in the study. The current study demonstrates a better diagnostic efficacy for HRCT when compared to chest X ray in the evaluation of interstitial lung disease.